Angle dependent structural colors with full-visible-spectrum and narrow-angle change properties for anti-counterfeiting. (December 2022) - Zhang, Rui; Yang, Zhiyu; Wang, Qing; Li, Wenchao; Xu, Huichen; Li, Long
Abstract: Photonic crystals (PCs) are widely investigated for applications in anti-counterfeiting, sensing, and displaying. And PCs exhibit obvious advantages over traditional pigments and dyes, including environmental friendliness, vivid structural colors, and color durability. However, less variety and low sensitivity of structural colors seriously limit their practical applications. Here, a nano-grating PC film, which featurs bright angle-dependent structural colors over the whole visible spectrum via small angle change, was made by the facile and low-cost inverted nanoimprint. By tuning the incidence angle from 25° to 60°, continuous structural colors can be perceived ranging from violet to wine accompanying red-shift of reflection peaks from 450 nm to 670 nm. Further, the film material of polydimethylsiloxane enables their mechanical flexibility and stability of the structural color. They can be readily patterned and applied as an anti-counterfeiting mark in university logo, which makes them promisingly practical as anti-counterfeiting materials. Highlights: Fabricating PC films by a facile and low-cost inverted nanoimprint lithography. PC films show colors over visible spectrum by change of incidence angle ∼30°. PC films have hydrophobic surface, flexibility and stable structural colors. Structural colors were easily patterned and used as anti-counterfeiting marks.